Characterization and thermal modeling of a miniature silicon vapor chamber for die-level heat redistribution. (May 2020) - Liu, Tanya; Dunham, Marc T.; Jung, Ki Wook; Chen, Baoxing; Asheghi, Mehdi; Goodson, Kenneth E.
Highlights: Miniature silicon vapor chambers can improve die-level temperature uniformity. Vapor chamber resistances are sensitive to a threshold liquid charge volume. Impact of liquid charge volume on resistance depends on wick microstructure effects. Abstract: Vapor chambers are passive heat spreaders that can improve system level temperature uniformity through efficient heat transport in a high effective thermal conductivity vapor core. Fabricating a vapor chamber out of silicon is highly appealing due to the potential for direct integration schemes with existing semiconductor devices, but may be impractical from a cost perspective if the size of the vapor chamber must be much larger than the die. We investigate the potential benefit to using a miniature silicon vapor chamber with an active vapor transport region of 1 × 1 cm 2 for the purpose of die-level heat redistribution. Due to the high amount of liquid charging precision required for working with such small-scale vapor chambers, a reduced order thermo-fluidic model is developed to predict the effect of both heat flux and liquid charge on the overall device thermal performance. The model incorporates wick microstructure effects and is validated against experimental results from a prototype device to agree within ±25%. The thermal performance of the vapor chamber is benchmarked against simulation results for solid silicon spreaders of comparable dimensions and is found to improve the hotspot temperature uniformity at heat fluxes above 60 W/cm 2 .